2004
DOI: 10.1093/jnci/djh133
|View full text |Cite
|
Sign up to set email alerts
|

Results of Two Open-Label, Multicenter Phase II Studies of Docetaxel, Platinum Salts, and Trastuzumab in HER2-Positive Advanced Breast Cancer

Abstract: Combinations of docetaxel, a platinum salt, and trastuzumab are feasible and active in patients with advanced breast cancers that overexpress HER2. The BCIRG is conducting ongoing randomized studies of the three-drug combination in both the metastatic and adjuvant settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
134
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(139 citation statements)
references
References 54 publications
1
134
0
3
Order By: Relevance
“…Pegram et al [26] reported the results of two phase II studies (BCIRG101 and UCLA-ORN) that evaluated triplets of trastuzumab, docetaxel and cisplatin or carboplatin. In both the studies an interesting response rate was obtained (ORR:79% BCIRG101; ORR:58% UCLA-ORN, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Pegram et al [26] reported the results of two phase II studies (BCIRG101 and UCLA-ORN) that evaluated triplets of trastuzumab, docetaxel and cisplatin or carboplatin. In both the studies an interesting response rate was obtained (ORR:79% BCIRG101; ORR:58% UCLA-ORN, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The humanized monoclonal antibody, trastuzumab (Herceptin), has been shown to improve survival in both adjuvant and advanced settings of breast cancer (12). Several studies in vitro and in vivo have shown that both additive and synergistic effects occur when trastuzumab is combined with chemotherapeutic agents (13)(14)(15)(16)(17). The synergistic effects of combining trastuzumab with cisplatin, carboplatin, and paclitaxel have been shown in several breast cancer cell lines (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39], this approach holds promise for increasing both response rate and duration relative to trastuzumab, and may expand the spectrum of antitumor activity of trastuzumab given alone or in combination with other antitumor strategies such as other cytotoxic agents (carboplatin, docetaxel; refs. [40][41][42][43], and/or antiangiogenic drugs (e.g., bevacizumab; anti-VEGF antibody, thrombospondin-1; refs. [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%